Face Recognition under Variation in Resolution Using Enhanced Local Ternary Pattern - Rani, Alka; Kumar, Narinder (International Journal of Computer Sciences and Engineering, 2018)
Face is an important biometric trait that has been used for various application of today’s technology. Face recognition comprises recognition of an individual identity to others on the basis of facial features. Facial features provide low accuracy due to variation in illumination and resolution of the images. In this paper an approach has been proposed that overcomes the issue of low recognition accuracy under low resolution captured images. In this paper texture features based approach that has been developed from the local ternary pattern by using two different groups of neighbour pixel values. On the basis of these two different groups texture features have been computed by comparing these values with centre pixel value of particular regions. By using local codes developed from the particular region whole image features have been computed using different codes from different regions. In this paper an approach that is combination of filtering and feature extraction has been proposed so that better face recognition can be achieved. On the basis of parameters analysis proposed work outperforms as compare to exiting approaches.